Pengaruh Kompensasi Dan Pengawasanterhadap Kinerja Karyawan Daerah Banjar Waterpark - Vina Zahra Nissa; Mila Karmila; Arga Sutrisna (Universitas Katolik Widya Karya Malang, 2023)
The purpose of this study was to find out and analyze the effect of compensation, supervision and employee performance on Banjar Waterpark regional companies. The research method used was a survey method with a quantitative approach, the sample of this study was 40 respondents who took a questionnaire. Sampling used saturated sampling technique and the method of analysis used was multiple linear regression analysis using SPSS 25 software. Based on the research results, the variables of compensation, supervision and employee performance are included in the good classification. The test results show that compensation partially has a significant effect on performance and supervision partially has a significant effect on performance. Simultaneously compensation and supervision have a significant effect on employee performance at Banjar Waterpark Regional Company.